AN OUTLOOK ON TOURISM DEVELOPMENT IN STAVROPOL KRAY - Dina Borisovna Chuprova (Вестник Северо-Кавказского федерального университета)
Discusses the history and prospects of development of tourism in the Stavropol territory. The analysis of various kinds of tourism in the region.